Gestational and lactational exposure to di-isobutyl phthalate via diet in maternal mice decreases testosterone levels in male offspring. (April 2017) - Wang, Xiaoyang; Sheng, Nan; Cui, Ruina; Zhang, Hongxia; Wang, Jianshe; Dai, Jiayin
Abstract: Phthalates are a large family of ubiquitous environmental chemicals suspected of being endocrine disruptors, with exposure to these chemicals during prenatal and postnatal development possibly resulting in reproductive disorders. Di-isobutyl phthalate (DiBP) is widely used in consumer and industrial products, and although its exposure in the general population has increased in recent years, the mechanisms behind DiBP-induced reproductive disorders in male offspring remain unclear. Here, pregnant mice were exposed to 0 or 450 mg/kg bw/day DiBP via diet from gestation day (GD) 0 to GD21. Until postnatal day 21 (PD21), half of the exposed pups were also exposed to DiBP by lactation (TT), while the rest were not (TC). Half of each group were sacrificed on PD21, with the remaining mice fed a normal diet until PD80 (TCC and TTC, respectively). Reproductive toxicological parameters such as relative organ weights and testosterone levels were determined in male offspring on PD21 and PD80 and sperm quality was tested on PD80. Maternal exposure (pregnancy and lactation) led to decreased serum and testis testosterone concentrations, accompanied by decreased expression of 3β-hydroxysteroid dehydrogenase (3β-HSD) and cytochrome P450 family 11 subfamily A member 1 (CYP11A1) in PD21 pups and PD80 adults. Furthermore, the TTC group showed decreased epididymis sperm concentration and motility. Taken together, DiBP exposure in early life (prenatal and postnatal) impaired male reproductive function in later life, possibly by interfering with testosterone levels and CYP11A1, which might be a major steroidogenic enzyme targeted by DiBP or other phthalates. Highlights: Maternal exposure to DiBP decreased offspring serum and testis testosterone levels. DiBP decreased expression of 3β-HSD and P450scc in PD21 pups and PD80 adults. Pre- and postnatal DiBP exposure impaired adult sperm concentration and motility.